DEVELOPMENT AND EVALUATION OF SUSTAIN RELEASE MICROPARTICLES OF METOPROLOL SUCCINATE - Sen, Suma Oommen; DEVBHUTI, PRITESH; SEN, KALYAN KUMAR; GHOSH, AMITAVA (International Journal of Applied Pharmaceutics, 2019)
Objective: In this study, xanthan gum was oxidized by sodium periodate to form xanthan dialdehyde. This oxidized gum was used as crosslinking agent as an alternative to somewhat toxic glutaraldehyde, the basis of which is the reaction between the Schiff reagent and the aldehydes formed by periodate oxidation. Methods: Formation of aldehyde groups were confirmed by Fourier Transform Infrared Spectroscopy (FTIR). Microparticles of metoprolol succinate were fabricated using crosslinking of a chitosan/gelatin mix system by dialdehyde Xanthan gum. The properties of the developed microparticles were investigated with swelling equilibrium studies, differential scanning calorimeter (DSC), in vitro drug release studies and scanning electron microscopy (SEM). Results: The in vitro drug release from these microparticles was affected by total polymer amount, oxidation reaction time and chitosan to gelatin ratio. The cumulative percent release of metoprolol succinate was observed within the range of 46 to 95% at 8 h from different formulations studied. The factors identified as significant to produce any impact on drug loading as well as drug release were both the polymer and inter actions of polymer and Xanthan gum dialdehyde. Conclusion: The release mechanism followed the super case II model kinetics.